Quantitation of Rosmarinic Acid and Caffeic Acid in Various Salvia Genera by High Performance Thin Layer Chromatography - Forough Karami; Samira Jaberi; Afshin Afsari; Mahmoudreza Moein (Shiraz University of Medical Sciences, 2020)
The plants with high amounts of polyphenolic constituents may act as antioxidants or as producer of other mechanisms causing to anticarcinogenic or cardioprotective actions. So, the objective of the present survey is quantitation of rosmarinic acid and caffeic acid as polyphenol compounds by means of high performance thin layer chromatography (HPTLC) in different Salvia genera such as Salvia santolinfolia, Salvia macilenta, Salvia comperesa, Salvia mirzayanii, and Salvia sharifii. The plant materials were collected from Hormozgan Province and methanolic extracts of them were studied by HPTLC. An HPTLC plate silica gel 60 F254 as stationary phase, toluene-ethyl acetate-formic acid with ratio of 67.72-22.90 and 9.38 %, repectively as mobile phase were selected and quantitation of rosmarinic acid and caffeic acid were done at 366 nm. It was found that S. comperesa (45.72±1.6 mg/g) and S. mirzayanii (464.64±0.028 mg/g) have higher amounts of rosmarinic acid and caffeic acid, respectively. Values of rosmarinic acid for other Salvia genera were obtained as; S. mirzayanii 8.50±0.46, S. santolinfolia 7.34±0.15, S. macilenta 5.64±0.18, and S. sharifii 4.52±0.11 mg/g for each of dried plants. Similar analysis for caffeic acid was achieved as 11.32±2.16 for S. santolinfolia, 5.22±1.13 for S. macilenta, 1.93±1.19 for S. comperesa, and for S. sharifii 4.63±3.26 mg/g for each of dried plants. In the developed method, Salvia officinalis was used as a standard module with amounts of 195.58 and 75.5 mg/g for rosmarinic acid and caffeic acid, respectively.